Pengaruh Tingkat Manajerial Sumber Daya Insani (SDI) Terhadap Kinerja Karyawan PT. BPRS Al-Wasliyah Medan - Suhairi, Suhairi; Lubis, Melisa; Sari, Reni Ilma; Safitri, Safrina (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
The purpose of this study was to determine the effect of human resource development: education and training, non-training activities, promotion and motivation on employee performance at PT. BPRS Al-Wasliyah in Medan. The data analysis used was multiple linear regression analysis to determine the effect of the independent variables (training & education, non-training activities, promotions and motivation) and the dependent variable (employee performance) with a fixed population and sample of 85 employees of PT. BPRS Al-Wasliyah in Medan 2023. Based on simultaneous data analysis, the variables of training and non-training education activities, promotion and motivation have a significant effect on employee performance at PT. Al-Wasliyah in Medan. While partially it is shown that the variables of education and training, promotion and motivation significantly influence the performance of employees at PT. Al-Wasliyah in Medan while non-training activity variables have no effect on worker performance.